A insurgência das margens: filosofia da diferença e um anarquismo por vir - Scienza, Roberto Corrêa (2022)
In this research we aim to fable an ethical proposal based on the crowned anarchy of difference. To do so, we start with the following problem: how to create an ethics beyond any morality in which others can affirm themselves as difference? In order to face this problem, we organize the thesis into six chapters: the first refers to a critique of Platonic and Aristotelian philosophies and their moralist presuppositions, which had a profound influence on Western thought. In this chapter, based on Deleuze, we explore the concepts of difference and identity, highlighting the moralist pillar on which these concepts were built. In the second chapter, we analyze the moral philosophies of Descartes, Kant and Hegel, from a Deleuzian perspective, taking into account the moralistic influence of Plato and Aristotle in their doctrines. In the third, we argue that the philosophy of difference is a philosophy of alterity and ethical creation, as well as we explore the actualization process of the conceptual pair difference and identity, a hierarchy that subordinates difference to identity and takes the other as a monster. The fourth chapter is dedicated to a discussion about Nietzsche's immoralism and the concept of will to power as an ethical movement beyond morality, enabling the creation of a post-moral ethics, which affirms the other as difference. In the fifth, we deal with the concept of fabulation as a political-philosophical strategy, a procedure capable of raising creative lines for the emergence of new ethics and modes of existence. In the sixth, we relate the crowned anarchy of difference to anarchism, establishing coherence between the critique of representation and morality in the philosophical sphere and the anarchist critique of representative politics and domination.